The South China Sea: Sub-basins, Regional Unconformities and Uplift of the Peripheral Mountain Ranges Since the Eocene - Franz L. Kessler; John Jong (Berita Sedimentologi, 2016)
This paper reviews the complex interaction of basin subsidence, erosion and uplift of mountain ranges that enclose the South China Sea (SCS). We found that recent uplift is a feature occurring dominantly at the fringes of the Sundaland Plate, around Sumatra/Java, Borneo, the Philippines and Taiwan. More significantly, there is a positive age correlation between regional unconformities, formation of oceanic crust and uplift of the peripheral mountain ranges. However, the magnitude of erosion related to each major unconformity can vary regionally, and could partly be subjected to climatic influence. The oldest truly regional unconformity recognizable is of very Late Oligocene age, and acts as an angular unconformity in Sabah, Sarawak, and the Malay/Penyu Basins (at Base ‘K’ level), at or very close to the base of the Miocene sedimentary package. We call this unconformity the Base Miocene Unconformity (BMU). Other than the BMU, the widely-known seismic event called the Mid-Miocene Unconformity (MMU) could be correlated with the end of proto-SCS spreading, and uplift may have occurred only in segments of the SCS, in particular at the southern fringe. The Late Miocene Shallow Regional Unconformity (SRU) points to a short compressive pulse that affected mainly areas of Sabah and Sarawak. The more recent Intra- Pliocene unconformity (IPU), commonly forming the base of some uplifted coastal terraces can be seen in particular in the south and eastern parts of the SCS, and correlates with uplift of areas such as NW Borneo and Taiwan. The event is a likely consequence of the Taiwan collision interplayed with the docking of the Philippines Plate in the Early Pliocene with NW Borneo at the Palawan/Philippines Margin. The Malay, Penyu, Natuna Basins and Vietnam Margin are predominantly Oligocene to Lower Miocene fills, whereas the NW Borneo Foredeep/Palawan Trough, deepwater Nam Con Son Basin and the Bunguran Trough have predominantly a Neogene fill.This observation points to a reduced extensional regime if compared with the south-eastern margin, where fault activity continued to the Mid/Late Miocene. The compiled uplift data in the surroundings of the SCS, as well as the presence of seismically mapped regional unconformities suggest that the greater Sundaland Plate has seen a number of extensions and compression/inversion/rotation phases; however there appears to be no positive evidence for the presence of microplates and/or subduction during the Oligocene/Miocene. In summary, crustal stretching, uplift and the resulting unconformities can be compared to different instruments of an orchestra playing individually; no harmonic tune can be achieved and there is little merit in looking at each contributing factor in isolation.